Extension of three-dimensional activity cliff information through systematic mapping of active analogs. Issue 54 (13th June 2015) - Hu, Ye; Furtmann, Norbert; Bajorath, Jürgen
<x xml:space="preserve">Abstract</x> Shown is a superposition of two analogs (green and orange) on crystallographic ligands (magenta and cyan) forming a three-dimensional activity cliff (MMP stands for Matched Molecular Pair).